Aid to agriculture in developing countries - Organisation for Economic Co-operation and Development (Paris Organisation for Economic Co-operation and Development., 1968)
This is a report prepared by the OECD secretariat to analyse the agricultural aid policies followed by member countries and international aid agencies. The report indicates that the share of the total volume of official aid developed to agricultural development around that period ( early and mid-1960$1 (Bs) had been inadequate. s
Includes bibliographical references.
lje 24/01/2018
Loans
Keywords: Agricultural assistance; Agriculture--International cooperation; Developing countries